Blood lactate concentration at selected of olympic modes weightlifting - Gupta, S.; Goswami, A. (Indian Journal of Physiology and Pharmacology, 2001)
This study highlights the blood lactate response of weightlifters (N = 5) in two modes of olympic lifts: Snatch (SN) and Clean & Jerk (CJ), during three types of training namely (1) one repetition lift (ORL), (2) Multiple set session (MSS) and (3) one set session (OSS). In ORL, 30, 40, 50, and 60 kg, each of one repetition only, were lifted with an interval of 5 min between two consecutive loads. Both MSS and OSS consisted of 6 sets of lift: 50% x 6 (i.e. 50% of 1 Repetition Maximum x 6 repetitions), 60% x 5, 70% x 4, 80% x 3, 90% x 2, and 100% x 1. In MSS, 3 to 3.5 min interval was given between two successive sets whereas in OSS the interval was approximately 24 hours. Lactate levels were very low (< 3.5 mM) in ORL. In MSS, lactate reached peak at an intermediate set, but, it was maximum at the first set and then declined gradually in OSS. In most of the cases, however, lactate were significantly higher in CJ than SN. The study concludes that: (a) anaerobic glycolysis is not stimulated considerably when the lifting time is only 4-5 sec, (b) repetition of lift plays more important role, than intensity, in lactate production, (c) CJ is more strenuous than SN for a given %RM.